The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1177/0271121415589546
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evaluation of the Implementation of a Routines-Based Early Childhood Intervention Model in Australia

Abstract: The aim of the current pilot study was to evaluate the implementation of a routines-based early childhood intervention (RBECI) model by Australian Early Childhood Intervention (ECI) professionals. The RBECI model consisted of four key components: (a) Routines-Based Interviews (RBIs), (b) participation-based goals, (c) home visits, and (d) community consultations. Five ECI professionals and nine families were recruited from an Australian ECI service. Professionals' ability to implement the model was assessed im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 26 publications
0
15
0
1
Order By: Relevance
“…Other studies have used the Goal Functionality Scale III (McWilliam, 2009), an earlier version of the tool, which included rating each criterion on a 1 ( not at all ) to 4 ( very much ) rating scale (Boavida et al, 2014; Boavida, Aguiar, McWilliam, & Correria, 2016; Hughes-Scholes et al, 2016; Rakap, 2015). Boavida and colleagues (2014) and Hughes-Scholes et al (2016) found results similar to those in the current study for the presence of GFS-III criterion related to necessity or usefulness and inclusion of an acquisition criterion. Rakap (2015), in a review of 100 individualized education programs developed for preschool children with disabilities in Turkey, found that professionals generally included skills that were necessary or useful ( M = 2.9) in goals, but were unlikely to include acquisition criterion ( M = 1.0).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have used the Goal Functionality Scale III (McWilliam, 2009), an earlier version of the tool, which included rating each criterion on a 1 ( not at all ) to 4 ( very much ) rating scale (Boavida et al, 2014; Boavida, Aguiar, McWilliam, & Correria, 2016; Hughes-Scholes et al, 2016; Rakap, 2015). Boavida and colleagues (2014) and Hughes-Scholes et al (2016) found results similar to those in the current study for the presence of GFS-III criterion related to necessity or usefulness and inclusion of an acquisition criterion. Rakap (2015), in a review of 100 individualized education programs developed for preschool children with disabilities in Turkey, found that professionals generally included skills that were necessary or useful ( M = 2.9) in goals, but were unlikely to include acquisition criterion ( M = 1.0).…”
Section: Discussionmentioning
confidence: 99%
“…For example, although IFSPs should include a statement of family’s resources, priorities, and concerns, the outcomes included in the document may not address these priorities and concerns (Jung & Baird, 2003). Outcome statements often do not address functional skills or lack specificity when identifying the skill, conditions for demonstrating the skill, or the criteria for knowing when the skill and outcome have been achieved (Bailey, Winton, Rouse, & Turnbull, 1990; Hughes-Scholes, Gatt, Davis, Mahar, & Gavidia-Payne, 2016; Jung & Baird, 2003; McWilliam, Ferguson, Harbin, Porter, & Vanderviere, 1998). Furthermore, family outcomes have been shown to be included rarely in the IFSP document, despite the encouragement to focus on the family as a whole (Boone, McBride, Swann, Moore, & Drew, 1998; Boone, Moore, & Coulter, 1995; Gallagher & Desimone, 1995; Jung & Baird, 2003; McWilliam et al, 1998; Polmanteer & Turbiville, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on RBT were examined under seven headings, including participant characteristics, dependent variable, independent variable, method, data collection tools, generalization, and maintenance. Upon examining the studies under the heading of participant characteristics, it was observed that in three of the studies, the early childhood intervention team and interventionist (Boavida et al, 2014;Boavida et al, 2016;Hughes-Scholes et al,…”
Section: Studies In Which Rbt Was Appliedmentioning
confidence: 99%
“…ÖZEL EĞİTİM DERGİSİ 837 2016), in two of the studies, families of children with developmental disabilities (Hughes-Scholes et al, 2016, Hwang et al, 2013, in one of the studies, the primary school teacher (Boavida et al, 2014), and in one of the studies, early childhood special education service practitioners (professionals and paraprofessionals) (Raab & Dunst, 2014) applied RBT.…”
Section: The Review Of Studies On Routine-based Teaching Practices Camentioning
confidence: 99%